Applying Flipped Classroom Model Using Duolingo Application to Enhance Thammislam Foundation School’s Student Learning EFL - Angelique Octaviani; Pirman Ginting (Indonesian Journal of Education and Mathematical Science, 2023)
Numerous research endeavors have been undertaken to formulate a flipped classroom learning model to enhance the caliber of education. However, integrating weblogs with the flipped classroom learning model has yet to garner significant scholarly scrutiny. The primary issue pertains to the need for more students' vocabulary acquisition. Consequently, individuals need help with attempting to engage in English language communication. Acquiring proficiency in a foreign language via the Duolingo platform offers a different and unique learning experience. Every educational system must incorporate a comprehensive set of methodological aspects that ensure the efficacy of the learning process. The elements above encompass monitoring progress, motivation, feedback, and vocabulary. The present study employs a quantitative descriptive research design. The research design used in this study is pre-experimental. This study employs a design that incorporates external variables which have the potential to impact the development of the dependent variable. The research utilized the Duolingo application as a tool for student engagement, accompanied by an observation sheet consisting of questions aimed at enhancing teachers' writing proficiency in the learning process. Additionally, post-test sheets were administered to assess the outcomes of the intervention. There is a total of 14 students classified as active, 14 students classified as moderately active, and 12 students classified as less involved. Based on the examination of student activity data, it can be inferred that 70% of student engagement with the flipped classroom approach, employing the Duolingo application for English language acquisition, falls within the active and moderately active classifications.